RELATIONSHIP AND LINGUOPOETIC CHARACTERISTICS OF OXYMORON AND PARADOX (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the relationship between oxymoron and paradox as interconnected yet independent linguopoetic phenomena. Although both devices are based on contradiction and the interaction of opposing concepts, they differ significantly in their structural organization, semantic mechanisms, and artistic functions. The study focuses on the syntactic and semantic realization of oxymoron in Uzbek literary discourse and compares its characteristics with those of paradox. Particular attention is paid to the mechanisms through which oxymoron creates aesthetic unity from semantic opposition, whereas paradox preserves contradiction as a logical and philosophical problem aimed at revealing deeper truths. The analysis demonstrates that oxymoron primarily functions as a syntactic-stylistic device, while paradox serves as a semantic-logical means of expressing unconventional judgments and stimulating intellectual reflection. The findings contribute to a clearer understanding of the linguopoetic nature of these phenomena and reveal the necessity of distinguishing between them in modern stylistic and linguopoetic studies.
Keywords: Oxymoron, paradox, linguopoetics, stylistics, semantic contradiction, syntactic structure, artistic discourse, aesthetic function, semantic opposition, Uzbek linguistics.